Not written in stone : Jews, constitutions and constitutionalism in Canada - Brown, Michael (Michael G.), 1938-; Elazar, Daniel Judah; Robinson, Ira, 1951- (Religions and beliefs series ;, 2003)
Using long-ignored constitutions of various Jewish organizations, this unique book uncovers the political history of Canadian Jewry since its beginning during the 1700s. Building on the premise that Jews, since time immemorial, have written down their values and ideologies, this study effectively demonstrates how these writings record the principles and values that motivated a community.